Göç ve toplum ruh sağlığı: Arafta kalan yaşamlar - Taycan, Okan; Uygun, Esin; Karabulut, Evindar (Toplum ve Hekim, 2020)
Özet: Göç neden olduğu zorlukların yanında pek çok imkân ve olanakları da barındırmaktadır. Zaten aksi de pek mantıklı olmazdı; yoksa insanlar niye evini, yurdunu, aşina olduğu bir yaşamı bırakıp bilinmezliğin kollarına atsın ki kendini? Bu yazıda çok katmanlı ve bir o kadar da karmaşık olduğu her halükarda kendini belli eden göç olgusu, toplum ruh sağlığı perspektifinden tartışılmaya çalışılmıştır.

Abstract: : In addition to the diff iculties caused by migration, it also involves many potentials and opportunities. Otherwise it wouldn’t make much sense; why would people leave their homes, countries, a familiar life and throw themselves into the arms of the unknown? In this article, the phenomenon of migration, which is multilayered and complex in any case, is tried to be discussed from the perspective of community mental health.
Keywords: göç; göçmen; mülteci; toplum ruh sağlığı; migration; immigrant; refugee; community mental health